SHORT STORY LEARNING MODEL BASED ON CREATIVITY DEVELOPMENT - Bambang Eko Hari Cahyono; Indrya Mulyaningsih (Universitas Negeri Makassar, 2020)
This study aimed to describe: (1) the short story learning conditions of the research setting, (2) the needs of students and lecturers about the short story learning model, (3) the development of the short story learning model based on creativity development, and (4) the effectiveness of the short story learning model based on creativity development. The results showed that 1) the short story learning process was teacher-centered and was theoretical and had not been able to develop student creativity; 2) produce a prototype of a short story learning model based on creativity development that has been validated by experts ; 3) conducting limited and extensive trials; 4) the creativity-based short story learning model was effective in improving students’ short story appreciation ability.